2016
DOI: 10.1186/s10194-016-0707-9
|View full text |Cite
|
Sign up to set email alerts
|

Headache service quality: evaluation of quality indicators in 14 specialist-care centres

Abstract: BackgroundThe study was a collaboration between Lifting The Burden (LTB) and the European Headache Federation (EHF). Its aim was to evaluate the implementation of quality indicators for headache care Europe-wide in specialist headache centres (level-3 according to the EHF/LTB standard).MethodsEmploying previously-developed instruments in 14 such centres, we made enquiries, in each, of health-care providers (doctors, nurses, psychologists, physiotherapists) and 50 patients, and analysed the medical records of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 17 publications
3
25
2
Order By: Relevance
“…Despite the differences in language and institutions (a university teaching hospital versus a private hospital), the findings were comparable in the two countries, suggesting operational validity in the evaluation of headache care. A subsequent pan-European study confirmed this in 14 specialist headache centres [7]. Further evaluations are nonetheless needed, and here we conduct a multicentre national study, extending implementation to the quality assessment of six Italian specialist headache centres (level three according to the EHF/LTB standard [8]) and examining acceptability and ease of use of the assessment instrument in another language and country.…”
Section: Introductionmentioning
confidence: 91%
“…Despite the differences in language and institutions (a university teaching hospital versus a private hospital), the findings were comparable in the two countries, suggesting operational validity in the evaluation of headache care. A subsequent pan-European study confirmed this in 14 specialist headache centres [7]. Further evaluations are nonetheless needed, and here we conduct a multicentre national study, extending implementation to the quality assessment of six Italian specialist headache centres (level three according to the EHF/LTB standard [8]) and examining acceptability and ease of use of the assessment instrument in another language and country.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, methods were developed for measuring headache service quality (service quality evaluation), and the Europe-wide study was the first to evaluate indicators for headache care to guide quality improvement [7]. This approach was also used for evaluating headache service quality indicators in six Italian specialist headache centres [8].…”
Section: Introductionmentioning
confidence: 99%
“… 2 Untreated or poorly managed headaches result in reduction of work productivity and economic consequences. 4 An assessment of the trigger factors of headache will be beneficial and important in the management of headache. 5 Moreover, the headaches which are presented to the secondary or tertiary care clinics are burdensome to the patients.…”
Section: Introductionmentioning
confidence: 99%